Evaluation of dentin remineralization with zinc oxide and calcium fluoride nanoparticles - An In vitro study - P Ahalya; K S Uloopi; C Vinay; Kakarla Sri RojaRamya; RamaKrishna Alla; P RangaRaju (Wolters Kluwer Medknow Publications, 2023)
Background: Partially demineralized dentin is remineralizable when mineral ions are made available in the near vicinity. Nanoparticles (NPs) have wide applications in remineralization process. Zinc promotes remineralization and has a synergistic effect when combined with fluoride. Hence, zinc oxide and calcium fluoride NPs were considered for dentin remineralization. Aim: The aim of this study was to evaluate the remineralizing ability of zinc oxide and calcium fluoride NPs on demineralized dentin individually and in combined form. Settings and Design: This was an in vitro study. Materials and Methods: Forty-eight dentin disks were prepared from the crowns of 12 extracted human molars and were allocated into four groups of 12 each, i.e., Group I - nano zinc oxide (nZnO), Group II - nano calcium fluoride (nCaF2), Group III - combined group (nZnO + nCaF2), and Group IV - artificial saliva (AS, control group). The specimens were demineralized with 37% phosphoric acid and placed in the respective remineralizing solutions for 24 h and 1 month. Calcium (Ca) and phosphorous (P) uptake was measured using energy-dispersive X-ray spectrometry, and structural changes were analyzed using scanning electron microscopy (SEM). Statistical Analysis: One-way analysis of variance, Student's t-test, and post hoc Tukey's test were used for statistical analysis. Results: At 1-month interval, all the groups showed an increase in Ca/P ratio, with highest being the combined group (4.24), followed by nCaF2 (3.30), nZnO (1.71), and AS (1.31) groups, and these differences were statistically significant (P = 0.000). On SEM analysis of dentinal samples at 1 month, depositions were evident in intertubular regions, wherein the highest deposits were observed in the nZnO group, followed by nZnO + nCaF2 and nCaF2 groups. Conclusion: Dentin samples subjected to remineralization with aqueous solutions of nZnO and nCaF2 showed an increase in calcium and phosphorous uptake and also dense granular depositions were evident in intertubular regions of dentin.